Entropy and the time evolution of macroscopic systems - Grandy, Walter T., 1933- (Oxford : Oxford University Press, 2008)
The work explicates the concept of entropy, particularly its governance of all of thermal physics, over a broad range of equilibrium and nonequilibrium phenomena. Historical development and modern research are presented in the context of entropy as a fundamental element of probability theory and its relation to information.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Entropy -- Statistical methods; Entropy (Information theory)